Unmet needs of patients with chronic obstructive pulmonary disease (COPD): a qualitative study on patients and doctors - Chia, Yook Chin; Wong, S.S.L.; Abdullah, N.; Abdullah, A.; Liew, S.M.; Ching, S.M.; Khoo, E.M.; Jiwa, M. (BMC, 2014)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic disease with repeated exacerbations resulting in gradual debilitation. The quality of life has been shown to be poor in patients with COPD despite efforts to improve self-management. However, the evidence on the benefit of self-management in COPD is conflicting. Whether this could be due to other unmet needs of patients have not been investigated. Therefore, we aimed to explore unmet needs of patients from both patients and doctors managing COPD.